A psychometric analysis of the reading the mind in the eyes test: toward a brief form for research and applied settings - Olderbak, Sally; Wilhelm, Oliver; Olaru, Gabriel; Geiger, Mattis; Brenneman, Meghan W.; Roberts, Richard D. (Frontiers in Psychology, 2015)
The Reading the Mind in the Eyes Test is a popular measure of individual differences in Theory of Mind that is often applied in the assessment of particular clinical populations (primarily, individuals on the autism spectrum). However, little is known about the test’s psychometric properties, including factor structure, internal consistency, and convergent validity evidence. We present a psychometric analysis of the test followed by an evaluation of other empirically proposed and statistically identified structures. We identified, and cross-validated in a second sample, an adequate short-form solution that is homogeneous with adequate internal consistency, and is moderately related to Cognitive Empathy, Emotion Perception, and strongly related to Vocabulary. We recommend the use of this short-form solution in normal adults as a more precise measure over the original version. Future revisions of the test should seek to reduce the test’s reliance on one’s vocabulary and evaluate the short-form structure in clinical populations.